Why listening to English is difficult for Spanish students - Eastman Curtis, John Kendall (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1991)
We examine the educational and cultural influences as well as some of the psychological and pedagogical factors which conspire to make listening comprehension difficult for Spanish students of English. We propose exercises which students should undertake as preparation and training for listening, and suggest an approach to the presentation and teaching of listening material.